HYPERSURFACES IN SPACE FORMS WITH SCALAR CURVATURE CONDITIONS - 徐森林 张运涛 (Acta mathematica scientia, 2004)
Let f : M^n→S^n+1真包含于R^n+2 be an n-dimensional complete oriented Riemannian manifold minimally immersed in an (n+1)-dimensional unit sphere S^n+1. Denote by S^n+1 the upper closed hemisphere. If f(M^n)包含于S+^n+1, then under some curvature conditions the authors can get that the isometric immersion is a totally embedding. They also generalize a theorem of Li Hai Zhong on hypersurface of space form with costant scalar curvature.